English Register and Its Contextual Meaning in COVID-19 Outbreaks Used in Indonesia - Diah Latifah Hanum Pratiwi; Fajar Susanto (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
The emergence of the COVID-19 outbreak has been gradually changing the condition, which caused the rise of some registers in society to describe the conditions that are impacted by the outbreak. As some of those registers already existed before the outbreak, thus, those registers automatically have different meanings adjusted by the condition or the context. This study aimed to analyze the registers during COVID-19, the contextual meaning of those registers, and how those registers are understood and used in society. In response to the problems, this study utilized descriptive qualitative research. In collecting the data, document review and unstructured interviews were applied, and the data obtained were analyzed by using content analysis. The result of this study revealed that; 1) there were fifteen English registers of COVID-19 found and used in Indonesia; 2) those registers have contextual meanings as it adjusted by the existing conditions; and 3) most of people understand those registers well, provided by their perceptions or thoughts that are close to the actual contextual meaning of those registers. Thus, it can be concluded that people comprehend those register clearly so that they can use those register properly.